2019
DOI: 10.7554/elife.47891
|View full text |Cite
|
Sign up to set email alerts
|

Epimutations are associated with CHROMOMETHYLASE 3-induced de novo DNA methylation

Abstract: In many plant species, a subset of transcribed genes are characterized by strictly CG-context DNA methylation, referred to as gene body methylation (gbM). The mechanisms that establish gbM are unclear, yet flowering plant species naturally without gbM lack the DNA methyltransferase, CMT3, which maintains CHG (H = A, C, or T) and not CG methylation at constitutive heterochromatin. Here, we identify the mechanistic basis for gbM establishment by expressing CMT3 in a species naturally lacking CMT3. CMT3 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(115 citation statements)
references
References 78 publications
10
105
0
Order By: Relevance
“…The observed levels were still an order of magnitude higher than the pure background noise that can be inferred from chloroplast methylation, especially in the case of CHG (1.16% CHG methylation on average over gene body compared to 0.22% background) ( Fig. S2, Table S1c), consistent with the known presence of low levels of non-CG methylation in gene bodies [31]. In terms of methylation in TEs, EM-seq produces similar metaplot pro les as WGBS, albeit with lower levels (especially for CHG and CHH ( Fig.…”
Section: Arabidopsis Dna Methylation Levels Measured By Em-seq and Wgbssupporting
confidence: 73%
“…The observed levels were still an order of magnitude higher than the pure background noise that can be inferred from chloroplast methylation, especially in the case of CHG (1.16% CHG methylation on average over gene body compared to 0.22% background) ( Fig. S2, Table S1c), consistent with the known presence of low levels of non-CG methylation in gene bodies [31]. In terms of methylation in TEs, EM-seq produces similar metaplot pro les as WGBS, albeit with lower levels (especially for CHG and CHH ( Fig.…”
Section: Arabidopsis Dna Methylation Levels Measured By Em-seq and Wgbssupporting
confidence: 73%
“…We speculate that additional data on DNA methylation in P. patens may reveal shared features of gene body methylation with M. polymorpha and with flowering plants. More shared features across land plants would provide additional support for the currently proposed model that gene body methylation may be a natural consequence of CMT3 function in the maintenance of heterochromatin (Wendte et al , ). Although bryophytes do not have CMT3‐clade CMT genes (Noy et al , ), de novo CG and CHH methylation activity of DNMT3 homologues in heterochromatic regions may provide a potential mechanism for how gene body methylation may arise in bryophytes (Yaari et al , ).…”
Section: Discussionmentioning
confidence: 75%
“…The functional and evolutionary significance of gene body methylation in the lineages of land plants is highly debated (Takuno et al , ; Zilberman, ; Bewick and Schmitz, ; Bewick et al , ; Wendte et al , ). Some studies have reported that gene body methylated genes are present in bryophytes, whereas others argued that they are just artefactual in origin (Zemach et al , ; Fulneckova et al , ; Takuno et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…CHH methylation can be classified as CWA (W = A or T) or non-CWA. DRM2 methylates CWA and non-CWA sites, and CMT2 preferentially methylates CWA nucleotides [53][54][55] . Only the edges of long heterochromatic TEs were hypomethylated in non-CWA contexts of post-embryonic nrpd1a mutant tissues relative to wild type ( Fig.…”
Section: Small Rna-directed Methylation Of Transposons During Embryogmentioning
confidence: 99%